Astrosismología de estrellas variables híbridas de secuencia principal - Sánchez Arias, Julieta Paz (2016)
Hybrid pulsating stars have an excellent asteroseismic potential since they show and -modes simultaneously excited, that allow to explore different regions of the stellar interior. In this study we present a theoretical modelling of five hybrid Sct- Dor stars recently discovered by the Kepler and CoRot spacial missions. In order to perform this study we developed numerical simulations of the evolution and pulsations of representative models of these stars, covering a wide range of parameters (stellar mass, effective temperature, overshooting parameter, metallicity). The huge bank of oscillation frequencies computed in this work allows us to carry out a detailed asteroseismic modelling of each of the target hybrid stars.